A Note on the Newman-Unti Group and the BMS Charge Algebra in Terms of Newman-Penrose Coefficients. (20th December 2012) - Barnich, Glenn; Lambert, Pierre-Henry
Abstract : The symmetry algebra of asymptotically flat spacetimes at null infinity in four dimensions in the sense of Newman and Unti is revisited. As in the Bondi-Metzner-Sachs gauge, it is shown to be isomorphic to the direct sum of the abelian algebra of infinitesimal conformal rescalings with 𝔟 𝔪 𝔰 4 . The latter algebra is the semidirect sum of infinitesimal supertranslations with the conformal Killing vectors of the Riemann sphere. Infinitesimal local conformal transformations can then consistently be included. We work out the local conformal properties of the relevant Newman-Penrose coefficients, construct the surface charges, and derive their algebra.